2012
DOI: 10.1007/s10645-012-9190-0
|View full text |Cite
|
Sign up to set email alerts
|

Are Occupations Paid What They are Worth? An Econometric Study of Occupational Wage Inequality and Productivity

Abstract: Labour economists typically assume that pay differences between occupations can be explained with variations in productivity. The empirical evidence on the validity of this assumption is surprisingly thin and subject to various potential biases. The authors use matched employer-employee panel data from Belgium for the years 1999-2006 to examine occupational productivity-wage gaps. They find that occupations play distinct roles for remuneration and productivity: while the estimations indicate a significant upwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 46 publications
4
20
0
Order By: Relevance
“…In different student, Cardoso et al [26] found that older employees' work capability increased at age 50-54, linear or remained stable up to age 59 and reduced afterwards. Nowadays, older employees serve as labor force to favor labor market condition of content in various sectors [27] such as public sector [23,28], private sector [29][30][31] and corporate sector [32][33][34]. Older employees are served as part of human capital enhancing economic development [35].…”
Section: Methodsmentioning
confidence: 99%
“…In different student, Cardoso et al [26] found that older employees' work capability increased at age 50-54, linear or remained stable up to age 59 and reduced afterwards. Nowadays, older employees serve as labor force to favor labor market condition of content in various sectors [27] such as public sector [23,28], private sector [29][30][31] and corporate sector [32][33][34]. Older employees are served as part of human capital enhancing economic development [35].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the measurement of productivity poses additional conceptual and methodological challenges that cannot easily be addressed in disaggregate studies. As noted by Vandenberghe (), “productivity is in essence a firm‐level phenomenon” in which the contribution of each individual, or even of groups of individuals, can often not be disentangled from the overall process of joint value creation within a firm (Kampelmann and Rycx ). As a consequence, “individual workers' productivity is hardly ever observed” and “the alignment of productivity and pay at the individual level is hard to assess” (Vandenberghe ).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…the fact that women face invisible but real barriers preventing them from obtaining higher-level positions. Indeed, results of Kampelmann and Rycx (2012) show that the occupation-pay profile in Belgian is steeper than the occupation-productivity profile. Accordingly, the fact that women are less likely to hold jobs at the upper rungs of the corporate ladder should ceteris paribus have a stronger detrimental effect on their pay than on their productivity.…”
mentioning
confidence: 99%